Correlation between Haller index and echocardiographic and spirometric findings in children with pectus excavatum - Alper Hazım Gürsu; Barbaros Şahin Karagün; Özlem Korkmaz; Sarper Şükrü Gürsu; Mehmet Ali Uçar (Türk Kardiyoloji Derneği Arşivi, 2014)
Objectives: In this study, we evaluated the correlation between severity of deformity and cardiopulmonary function with regards to echocardiographic and spirometric findings. Study design: Twenty-five children, mean age 13.6 years, presenting with pectus excavatum between August 2012 and May 2013, were included. Haller index (HI) was calculated for each patient. Patients with an index of <2.5 were accepted as Group 1, 2.5-3.6 as Group 2, and >3.6 as Group 3. Left ventricle dimension, ejection fraction, and shortening fraction were evaluated with echocardiography. Using spirometry, forced vital capacity (FVC), forced expiratory volume in the first second (FEV1), and FEV1/FVC ratio were calculated. Groups were compared using these parameters. Results: There were 18 males and 7 females. The mean index was 3.48+-0.78. Though there was no significant difference in the index with regards to sex, the index increased with age. Eight percent of patients were in Group 1, 52% in Group 2 and 40% in Group 3. A significant decrease in ejection and shortening fractions was evident as the index increased. A statistically significant relation between HI and cardiac dysfunction was evident (p<0.01). As the index increased, there was significant decrease in FEV1 and the FEV1/FVC ratio, while there was no significant difference in FVC. As the deformity worsened, incidence of pulmonary dysfunction was found to be higher. Conclusion: This study revealed that pectus excavatum leads to cardiac and pulmonary problems, and functions of the left ventricle may be affected by the deformity. Furthermore, the relation between the severity of the deformity and cardiovascular function is evident.